Investigation of Biochemical Effect of Phenols Extract Isolated from Coriandrum sativum Seeds Against Echinococcus granulosus Parasite in Vitro - Dawwas, Abbas (University of Thi-Qar Journal of Science, 2019)
This study was carried out to investigate effect of phenols extract isolated from Coriandrum sativum seeds extract against Echinococcus granulosus parasite gotten from livers of sheep infected by hydatid disease in Basrah abattoir . It was found that increase of concentration of extract led to decrease of protoscolices viability and the number of dead protoscolices increased with increase of days . Also the concentration of (0.75 gm/ml) had the higher effect on viability of protoscolices where it was noticed that this concentration killed all protoscolices after three days of treatment wheras the concentration of (0.25 gm/ml) was the less effect where it led to kill protoscolices after seven days of treatment with extract . The viability percentage reached to zero at concentration of (0.75 gm/ml) in the third day but at concentrations (0.5 and 0.6 gm/ml) was zero in the fourth day . Also it was found that protoscolices viability percentage was zero in the seventh day of treatment by using concentration of (0.25 gm/ml) . Therefore phenols extract concentration of (0.75 gm/ml) can be used as a medicinal herbal substitute instead of antibiotics but it needs further clinical studies .